Analisis kesalahan penggunaan bahasa dalam karangan teks eksplanasi peserta didik kelas V SD - Solehah, Adinda Miftakhul; Slamet, St Y; Surya, Anesa (Universitas Sebelas Maret, 2023)
The purpose of this study was to identify and describe the forms of language use errors in the form of spelling, diction, and sentences and to determine the factors of language use errors in explanatory text compositions for fifth grade student at SDN Tegalayu Surakarta. The research is a qualitative research with a case study approach that focuces on a phenomenon.The data collection techniques used were document analysis, observation, and interviews. Test the validity of the data used data sources triangulation and technical triangulation. The data analysis technique used is interactive analysis. The most errors in language use were found in spelling errors with 80.37%, followed by diction errors 14.27%, and sentence errors 5.36%. Factors causing errors in the use of language come from two factors, factors from the teacher in the form of writing learning strategies that are too simple and not doing an analysis of essay errors and factors from students in the form of students lack of understanding of the rules of language use, lack of student vocabulary, and lack of motivation to write. So that teacher can provide many example of good essay before writing and repeated writing exercise.